HUBUNGAN ANTARA DUKUNGAN SUAMI DENGAN KECEMASAN SELAMA PERSALINAN PADA PRIMIGRAVIDA DI PUSKESMAS MLATI II SLEMAN - Retnowati, Retnowati; Mawarti, Retno; Yati, Dwi (Universitas Jenderal Achmad Yani Yogyakarta, 2016)
Background: Labor is the process of delivering a baby that occurs in full-term pregnancy (37-42 weeks). One of the efforts to reduce anxiety during labor is to provide support from a significant person, a husband. Husban’s support in labor process is a source of strength for woman who cannot be replaced by health personnel. Objective: To identify the relationship between husband’s support and anxiety level during labor on primigravida at Mlati II Health Center Sleman. Methods: This study was descriptive quantitative, with cross sectional approach. The samples were 20 respondents who were selected withaccidental sampling technique. Research employed questionnairesto measure husband’s support and mother’s anxiety level. Study used univariable and bivariable analysis. Result: Most of the husband's support during labor on primigravida at Mlati II Health Center Sleman were at high category (75.0%). The majority of mothers experienced mild anxiety (50.0%). The relationship between husband’s support and anxiety during childbirth in primigravida mother at Mlati II Health Center Sleman district was at strong category; r = -0.632 (.600 to .799). Conclusion : There was a relationship between husbands’ support andprimigravida mothers’ anxiety level during labor at Mlati II Health Center Sleman.